Noise, Now: Listening to Networks - Crawford, Kate (Meanjin, 2010)
The constant and increasing connectedness among people through electronic communications such as Twitter, text messages and e-mail is criticised. It is believed that such information overload is addictive and unnecessary, and some disconnected and isolated time for the individual self is essential.